Independence of Resistance in Brachiaria spp. to Nymphs or to Adult Spittlebugs (Hemiptera: Cercopidae): Implications for Breeding for Resistance - Cardona Mejía, César; Miles, John W.; Zuniga, G; Sotelo, G. (Oxford University Press, 2010)
Both nymphal and adult spittlebugs (Hemiptera: Cercopidae) cause serious economic damage to susceptible brachiariagrass [genus Biachiaria (Trin.) Griseb], pastures in tropical America. Both life stages are xylem feeders: nymphs feed primarily on roots and stems, whereas the adults feed mainly on foliage. Numerous interspecific brachiariagrass hybrids with high levels of antibiosis resistance to nymphs of several important spittlebug species have been obtained. Recent studies revealed major inconsistencies between reaction to nymphs and reaction to adults on the same host genotype. Because both insect life stages can cause severe economic damage on susceptible brachiariagrass pastures, a cultivar development strategy must take into account resistance to both life stages. To assess the degree of association between resistance to spittlebug nymphs and to adult feeding, we tested 164 hybrids and six check genotypes for resistance to both life stages of three spittlebug species: Aeneolamia varia (F.), Aeneolamia reducta (Lallemand), and Zulia carbonaria (Lallemand). Most hybrids tested were classified as resistant to nymphs. On the contrary, for all three species, the overall mean damage score of the 164 hybrids did not differ from the mean score of the susceptible checks. None of the hybrids was classified as resistant to adult feeding damage. Correlations between percentage nymph survival and adult damage scores were consistently low (r = 0.0104–0.0191). Correlations between nymphal and adult damage scores were also low (0.109–0.271), suggesting that resistances to the different life stages are largely independent. Chi-square analyses comparing frequency distributions of responses of the 164 breeding hybrids to nymphs or adults confirmed essential genetic independence of these two traits. We conclude that attention to improving genetic resistance specifically to adult feeding damage is warranted.